Optimal savings distortions with recursive preferences - Farhi, Emmanuel 1978-2020; Werning, Iván 1974- (National Bureau of Economic Research, 2008)
This paper derives an intertemporal optimality condition for economies with private information, focusing on a class of recursive preferences. By comparing it to the situation where agents can freely save in a risk-free asset market, we derive the optimal savings distortions necessary for constrained optimality. Our recursive preferences are homogeneous and satisfy a balanced growth condition, while allowing us to separate the role of risk aversion and intertemporal elasticity of substitution. We perform some quantitative exercises that disentangle the respective roles played by these two parameters play in opt8imal distortions and the implied welfare gains.